Tourism Informatics 2010
DOI: 10.4018/978-1-60566-818-5.ch014
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Photographs on Consumer Generated Content Websites

Abstract: Word-of-mouth is an important source of information for tourists making decisions about what destinations to visit. Word-of-mouth has a strong influence on shaping the image of a destination, particularly for remote destinations which are in part characterised by limited market penetration in terms of more formal marketing communications. There has been some research situating consumer generated content in Web 2.0 applications as word-of-mouth that has the potential to influence destination images for some des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Travel is a unique visual experience, and vacation photos are important components of travels. The "slideshows and photographs are a common way to communicate personal trip experiences and perceived destination images" [40] (p. 245).…”
Section: B Destination Image and Photosmentioning
confidence: 99%
“…Travel is a unique visual experience, and vacation photos are important components of travels. The "slideshows and photographs are a common way to communicate personal trip experiences and perceived destination images" [40] (p. 245).…”
Section: B Destination Image and Photosmentioning
confidence: 99%
“…A study by Lo et al (2011) reveals that 89% of pleasure travelers take photographs and that 41% of them post their photographs online. SNSs, such as FB, have made personal travel photos visible to the public (Boyd, 2008; Miller and Edwards, 2007; Qian and Scott, 2007), expanding the potential audience beyond family and friends to new people living worldwide (Goodman, 2007; Schmallegger et al, 2010). These result in a larger number of people see personal travel photos or videos, and read personal posts and statuses about travel destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sojourners exercised variety in the composition of the images, where all 10 photo regions identified by Yang et al (2007) were observed. The majority of images in this category featured people performing or engaging in the events (Figure 3), where the inclusion of others adds to the atmosphere, conveying the notion of a fun, friendly, vibrant, and active community (Schmallegger et al, 2010; Urry, 1992).…”
Section: Data Analysis and Findingsmentioning
confidence: 99%
“…Globally, millions of user-generated images (UGI) are shared each minute, and the numbers are predicted to rise given the pervasiveness of online networking platforms and mobile devices fitted with cameras. UGI represent visual articulations of personal experiences, and are today imperative sources of travel inspiration (Cohen et al, 2022; Schmallegger et al, 2010). The importance of UGI in shaping consumer perceptions of destination image and travel decisions have resulted in the reconfiguration of traditional marketing practices—in a bid to leverage the reach, and perceived trustworthiness tied to online consumer networks (Dinhopl & Gretzel, 2016; Dwivedi et al, 2021; Volo & Irimiás, 2021).…”
Section: Introductionmentioning
confidence: 99%